Spleen and Bilateral Kidney Infarction and Intestinal Ischemia Due to Atrial Fibrillation - Gurel, Ali; Atli, Hasan; Duzenci, Deccane; Dogukan, Ayhan; Ulu, Ramazan; Gozel, Nevzat (Turk Nefroloji Diyaliz Transplantasyon Dergisi, 2016)
We report a 82-year-old women who presented with abdominal pain, nausea and multiple organ ischemia and infarction due to atrial fibrillation (AF). Her electrocardiography (ECG) was compatible with AF and the transaminase and creatinine levels and leukocyte counts were high. In addition to anticoagulation, supportive treatment was administered. After treatment her complaints decreased and the elevated laboratory parameters returned to nearly normal ranges. Abdominal symptoms of patients with atrial fibrillation should warn physicians regarding ischemia and infarction that may occur in abdominal organs.
Keywords: Spleen; Kidney; Infarction; Intestinal ischemia; Atrial fibrillation